7 - Food Price Changes and Consumption Adaptation Models In Enugu State, Nigeria Amidst Covid-19 Pandemic Shocks - Ifejirika, Chika; Mkpado, Mmaduabuchukwu (Africa Development, 2024)
The Covid-19 pandemic was a global disaster that affected the food security status of the world. This article examined food price changes and consumption adaptation models in Enugu State, Nigeria, to ascertain people’s consumption patterns and the usefulness of palliative measures given to them. Primary data was generated through a survey of eighty respondents. The secondary data was compiled from monthly reports of food prices by the National Bureau of Statistics and was analysed using descriptive statistics, the Consumer Price Index and chi-square tests. The price indices of food items like white garri and sweet potatoes showed very high inflation during the pandemic period. The number of households who ate only once a day increased, and those who ate three times a day decreased. The chi-square result on differences in eating habits and meal regimen before and during Covid-19 is significant. Many of the respondents received palliative aid during the pandemic. The article recommends that the government should encourage farmers to increase their production by providing them with loans and subsidies so that they may produce enough food in times of emergency like the pandemic.